1999
DOI: 10.1007/s004050050166
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent respiratory papillomatosis associated with gastroesophageal reflux disease in children

Abstract: The hallmark of gastroesophageal reflux disease (GERD) is an increased exposure of esophageal and laryngeal mucosa to gastric juice. This exposure can cause complications such as chronic laryngitis or chronic respiratory diseases. We report our experience in managing three pediatric patients with severe recurrent juvenile laryngeal papillomatosis (JLP) associated with GERD. All patients showed a high rate of recurrence requiring multiple laser surgeries. Systemic alpha interferon therapy over a period of more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 18 publications
1
40
0
2
Order By: Relevance
“…Other antiviral drugs (e.g., acyclovir and valacyclovir), and indole-3-carbinol were also used in small series [1,2,16,[19][20][21][22]. According to a limited number of studies, the effective management of laryngopharyngeal reflux may also result in an improved control of RRP [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…Other antiviral drugs (e.g., acyclovir and valacyclovir), and indole-3-carbinol were also used in small series [1,2,16,[19][20][21][22]. According to a limited number of studies, the effective management of laryngopharyngeal reflux may also result in an improved control of RRP [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…5) Risk factors leading to virus activation in RRP have not been recognized; however, gastroesophageal reflux disease has been suggested as a possible factor. 10) Malignant degeneration into squamous cell carcinoma occurs in 3% to 5% of papilloma patients and more often in patients with a history of smoking or radiation therapy. However, other risk factor for malignant transformation has been noted.…”
Section: Discussionmentioning
confidence: 99%
“…22 Other authors have found a potential relation between the severity of RLP and gastroesophageal reflux. 8,11 Furthermore, recent papers have shown that most of the surgical complications of RLP patients, such as scars, laryngeal membranes, and airway stenosis are late complications and tend to be more significant and frequent in patients with gastroesophageal reflux. 22 Based on our study, we believe that the treatment of reflux may be a further treatment strategy to control this high morbidity disease.…”
Section: Discussionmentioning
confidence: 99%
“…7 Borkowski et al in 1999 first suggested a correlation between RLP and gastroesophageal reflux by showing that controlling reflux resulted in reduced growth of laryngeal papillomas. 8 At the same time other authors started to note that gastroesophageal reflux was very frequent in RLP patients, and that this condition could also be associated with other laryngeal disorders such as recurrent croup, subglottal stenosis and vocal nodules. 9,10 The HPV virus in RLP causes recurrence, and may remain latent in the laryngeal mucosa for an unknown time.…”
Section: Introductionmentioning
confidence: 99%